Community-Based Restorative Justice for Offenders With Mental Disorders in Indonesia - Isnawan, Fuadi (Universitas Semarang, 2025)
This study analyzes the implementation of restorative justice in handling theft committed by individuals with mental disorders in rural Indonesia, focusing on its compatibility with human rights and social rehabilitation principles. The research was motivated by the recurring challenge of criminalizing mentally disordered offenders without adequate medical and social considerations, leading to ineffective deterrence and recurring offenses. Using a normative juridical method with a qualitative descriptive approach, the study examines statutory provisions, legal doctrines, and empirical practices involving the prosecution and correctional systems. The findings reveal that restorative justice offers an alternative framework that emphasizes accountability, rehabilitation, and social reintegration rather than punitive measures. However, its application remains inconsistent due to limited institutional understanding, a lack of coordination between law enforcement and mental health institutions, and inadequate legal infrastructure in rural areas. The novelty of this research lies in its integration of restorative justice with mental health protection as a model for humanizing criminal law enforcement. The study concludes that the restorative justice approach can effectively bridge the gap between criminal responsibility and medical treatment, thereby promoting a more humane, inclusive, and community-based justice system in Indonesia.